MENTAL HEALTH AND WELL-BEING OF THAI YOUTH: ADDRESSING THE GROWING CRISIS - Ransri, Jesadakorn (วารสารวิชาการสังคมศาสตร์สมัยใหม่ (Online), 2024)
This paper explores the growing mental health crisis among Thai youth, examining the key contributing factors such as academic pressure, family dynamics, social media, and economic inequality. The impact of mental health issues on education, social relationships, and long-term physical health is discussed, highlighting the barriers that prevent youth from accessing adequate mental health care. The paper reviews current initiatives by the Thai government, non-governmental organizations (NGOs), and schools, and proposes recommendations to address the crisis. These include increasing mental health awareness, expanding access to services, training for parents and teachers, and utilizing technology for teletherapy. The urgency of addressing youth mental health is emphasized, with a focus on the long-term consequences of inaction and the potential for Thailand to become a leader in mental health interventions through policy reform and education.